Applicability of Activities Listed in Modified Falls Efficacy Scale (MFES) In Indian Elderly (International Journal of Physiotherapy, 2025)
Background: Falling is a major public health concern among the elderly. Fear of falling (FF) is a significant issue leading to the self-avoidance of regular physical activities, and the Modified Falls Efficacy Scale (MFES) measures the fear of falls in the elderly. However, in MFES, out of 10 indoor and 4 outdoor activities, not all activities are relatable to the Indian population. In contrast, some typical activities with a high risk of falls are not included. Hence, the study aims to assess the applicability of activities listed in MFES in the Indian elderly.Methods: 104 elders, both males and females, from the community and institutions were evaluated. The MMSE and Geriatric Depression Scale were evaluated for cognition and depression symptoms. The risk of falls was assessed with TUG. Subjects were interviewed with MFES about their confidence level and the applicability of activities. Subjects were asked about any other activity that gives them fear of falls, which was not in MFES.Results: Pearson’s Chi-square test revealed significant values (p